The Alström syndrome: ophthalmic histopathology and retinal ultrastructure. Issue 7 (July 1984) - Sebag, J; Albert, D M; Craft, J L
Abstract : A case of pigmentary retinal degeneration causing blindness in early childhood, progressive neurosensory hearing loss, diabetes mellitus, acanthosis nigricans, hypogonadism with normal secondary sex characteristics, and kyphoscoliosis without polydactyly and with no mental retardation is reported. The results of endocrinological studies, karyotype analysis, and digital dermatoglyphics supported the clinical diagnosis of the Alström syndrome. The patient had small globes, bilateral posterior subcapsular cataracts, lacy vacuolation of the iris, ciliary process hyalinisation, unilateral asteroid hyalosis, total absence of rods and cones, intraretinal melanin pigment, retinal pigment epithelium atrophy, focal chorioretinal fusion, preretinal fibrosis, bilateral giant optic disc drusen, and optic nerve atrophy. Electron microscopy of the retina demonstrated large numbers of melanolysosomes, numerous folds of basement membrane material, disruption of Bruch's membrane, and numerous bundles of extracellular collagen fibrils in the retinal pigment epithelium.